EDUKASI DAMPAK ANEMIA PADA IBU HAMIL - idyawati, susilia; Ricca Afrida, Baiq; Putu Aryani, Ni; Hawari Jannati, Sri; Jannah, Raudatul (Stikes Yarsi Mataram, 2024)
Anemia of pregnant women is a condition where the hemoglobin level in the blood of pregnant women is less than 11g%. If the condition of anemia in pregnant women is not treated, it will cause complications that occur in the mother during pregnancy, childbirth, postpartum and also have an impact on the fetus she is carrying. The aim of this service is to increase the knowledge of pregnant women about the impact of anemia. The implementation method for this activity includes the preparation, implementation and evaluation stages. In the preparation stage, examinations and outreach are carried out to pregnant women, especially pregnant women with anemia, then providing assistance and education about the impact of anemia. At the implementation stage, TTV checks will be carried out and early detection of anemia by carrying out Hb checks, then education will be carried out about the impact of anemia on pregnant women and coaching will be carried out. Before the counseling was carried out, a pre-test was carried out on 15 pregnant women with 65% of pregnant women having sufficient knowledge and 35% lacking knowledge and after conducting the counseling, it was found that the mothers' knowledge of anemia was 80% good and 20% very good.